INVENTARISASI JENIS PAKU-PAKUAN (PTERIDOPHYTA) TERESTERIAL DI JALUR PENDAKIAN NOKILALAKI KAWASAN TAMAN NASIONAL LORE LINDU - Erwin Taslim; Ramadanil Ramadanil; Samsurizal M Sulaeman (Biocelebes, 2019)
Research on "Inventory of terrestrial fern species in The Nokilalaki Climbing Route Of Lore Lindu National Park in Tongoa village, Nokilalaki district, Sigi regency of Central Sulawesi province" was carried out in May to July 2016. This study aims to know the type Any kind Of terrestrial spikes found on the nokilalaki climbing lane national park. This research uses Exploratory Method that is to explore the area of climbing path Nokilalaki, starting from the bottom point of the line that is from shelter 1 to shelter 4 or peak. It also collects specimens of Terrestrial Nail Plants for the manufacture of Herbariums or plants. The herbarium sample is used for identification process. The identification process is done in biodiversity laboratory majoring in biology faculty of mathematics and natural sciences, Tadulako University using book “Fern of malasya in colour dan prosea’’And compare it with the collection contained in the biodiversity lab. The results showed 23 species of nail plants consisting of 14 genera and 10 families and 3 unidentified species.